The role of eLearning in health management and leadership capacity building in health system : a systematic review - Tudor Car, Lorainne (2018)
Background: Health leadership and management are essential for ensuring resilient health systems. Relevant training opportunities are often scarce, and the use of digital education could help address this gap. Our aim was to assess the effectiveness of eLearning for healthcare leadership and management capacity building. Methods: We performed a systematic review on the effectiveness of eLearning for health leadership and management training. We also reviewed literature on relevant competencies and training programmes. We conceptualise the role of health leadership and management capacity building in health system strengthening and explore the use of eLearning in this area. Results: No evidence was found on the effectiveness of eLearning for health leadership and management capacity guiding. Evidence on health leadership and management education effectiveness in general is scarce and descriptive and reports learning outcomes. We explore how various forms of eLearning can help meet specific requirements of health leadership and management training. Conclusions: Literature on the effectiveness of health leadership and management education is scarce. The use of eLearning could support this type of training by making it more accessible and tailored. Future research should be carried out in diverse settings, assume experimental designs, evaluate the use of information technology and report health system outcomes.